2019
DOI: 10.3390/ijms20205009
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Membrane and Biological Target on the Structural and Allosteric Properties of Recoverin: A Computational Approach

Abstract: Recoverin (Rec) is a prototypical calcium sensor protein primarily expressed in the vertebrate retina. The binding of two Ca2+ ions to the functional EF-hand motifs induces the extrusion of a myristoyl group that increases the affinity of Rec for the membrane and leads to the formation of a complex with rhodopsin kinase (GRK1). Here, unbiased all-atom molecular dynamics simulations were performed to monitor the spontaneous insertion of the myristoyl group into a model multicomponent biological membrane for bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 50 publications
(73 reference statements)
0
16
0
Order By: Relevance
“…It should be noted that our simulation strongly suggested that lipid raft formation was essential for the formation of the row of Rh dimers, but did not suggest much about the molecular mechanism of lipid raft formation. In order to reveal the detailed mechanism of lipid raft domain formations, we need to consider various other physicochemical properties of lipids, such as the electrostatic properties of the polar head [44,45], as well as, the effects of cholesterols by the considering molecular models with microscopic details; this is one of our future challenges. On the other hand, we expect to obtain results that are similar to Coarse-grained molecular dynamics simulation of rhodopsin aligned oligomer formation the ones presented, if such physicochemical properties of lipids play weak or positive roles in raft formation.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that our simulation strongly suggested that lipid raft formation was essential for the formation of the row of Rh dimers, but did not suggest much about the molecular mechanism of lipid raft formation. In order to reveal the detailed mechanism of lipid raft domain formations, we need to consider various other physicochemical properties of lipids, such as the electrostatic properties of the polar head [44,45], as well as, the effects of cholesterols by the considering molecular models with microscopic details; this is one of our future challenges. On the other hand, we expect to obtain results that are similar to Coarse-grained molecular dynamics simulation of rhodopsin aligned oligomer formation the ones presented, if such physicochemical properties of lipids play weak or positive roles in raft formation.…”
Section: Discussionmentioning
confidence: 99%
“…This group can, therefore, be considered as important retinal calcium-binding proteins. This observation is consistent with the literature: CaBP4 is localised in photoreceptor synaptic terminals and is essential for neurotransmission between photoreceptors and bipolar cells as part of the Cav1.4 channel complex in the retina [ 35 ]; CaBP5 in mice is expressed in type 5 ON-cone bipolar cells, and in type 3 OFF-cone bipolar cells as well as in rod bipolar cells [ 36 , 37 , 38 ]; Guca1b is important for rod cell recovery after light exposure, by stimulation of guanylate cyclases in these photoreceptors [ 39 ]; Secretagogin plays an essential role in synapse maturation and in mouse, rat, and rabbit retina it is expressed in subtypes of cone bipolar cells, but cannot be detected in the rod bipolar cells [ 40 ]; Recoverin is thought to be a calcium sensor in retinal rod cells that can control the lifetime of photoexcited rhodopsin by inhibiting rhodopsin kinase [ 41 , 42 ]; and last but not least Plch1 has been shown to be expressed in mouse and human retina as well [ 43 ].…”
Section: Search For New Cabps Detailed Analysis Of Rna-seq and Ish Databasesmentioning
confidence: 99%
“…On the other hand, prompt sequestration of the myristoyl group in the protein milieu at low [Ca 2+ ] is essential to permit GRK1 function. While both experimental studies [ 21 , 23 ] and molecular dynamics simulations [ 24 , 25 ] are consistent with the notion that Ca 2+ -bound mRec stabilizes the R state and allows the spontaneous insertion of the myristic moiety into the ROS disc membrane, the low apparent affinity ( K D app = 17–18 µM) for Ca 2+ binding of mRec in aqueous solution raised concerns as to the actual role of Rec in vivo [ 26 28 ], where [Ca 2+ ] varies in a narrow sub-micromolar range (20–250 nM in mouse rods [ 29 ], but see ref. [ 30 ] for higher values in other vertebrates).…”
Section: Introductionmentioning
confidence: 99%